The Teaching Writing of English as a Foreign Language in Senior High School: A Qualitative Analysis of Students’ Perceptions in Indonesia - Fauziah, Adelia Noor; Ithriyah, Siti (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The focus and purpose of this research are to investigate students’ perceptions of teachers who teach writing in the classroom and how student’s expectations of English writing instruction in the classroom to improve their writing skills. This study, which took a qualitative approach, gathered information from ten students via an open-ended questionnaire and observation to explore their perceptions of teaching English writing as a foreign language. This study’s key finding is how crucial it is to teach English writing in the classroom using the right methods. If suitable instructional methodologies, strong teacher support, and the use of pertinent materials are applied to English writing instruction, students can improve their writing skills. Additionally, success in the classroom and in the future workplace depends on possessing strong English writing abilities.